PERAN STRATEGIS TOP MANAGEMENT TIM (TMT) DALAM ORGANISASI: SEBUAH TELAAH KRITIS DAN EVALUASI TERHADAP STUDI DALAM KONTEKS ASIA - Fadhliah Alhadar (Optimum: Jurnal Ekonomi dan Pembangunan, 2012)
It has been widely recognized that organizational productivity is highly depend on the strategic role of top management team (TMT). The team has critical functions in producing key decisions for sustaining organizational competitive advantage. A numbers of empirical findings also support the fact that the effectiveness of TMT associates with various critical outcomes. Unfortunately, TMT also facing some potential conflict as it consists of various members’ diverse backgrounds. How TMT can manage conflict effectively, therefore, has been one of the key success factors in fostering the team effectiveness, which eventually benefits the organizational process. This article exclusively reviews the importance of TMT as a strategic team in organization by evaluating the study of Chen, Liu dan Tjosvold (2005) that investigates how TMTs in Asian context (China) manage conflicts can greatly contribute to their effective leadership of organizational innovation. In discussing team diversity, conflict management and organizational innovation, the article integrates various concepts, empirical findings and methodological issues from the literature.